Iodine-123 phenylpentadecanoic acid myocardial scintigraphy in patients with left ventricular hypertrophy: Alterations in left ventricular distribution and utilization - Wolfe, Christopher L.; Kennedy, Patrick L.; Kulkarni, Padmaker V.; Jansen, Donald E.; Gabliani, Gregory I.; Corbett, James R. (The American heart journal, 1990)
Regional alterations in myocardial substrate uptake and/or utilization have been demonstrated in rats with hypertension. To determine whether alterations in left ventricular fatty acid uptake and/or utilization are present in patients with left ventricular hypertrophy (LVH), we compared the results of rest and exercise iodine-123 phenylpentadecanoic acid (IPPA) myocardial scintigraphy in 10 patients with hypertension who had concentric LVH without evidence of coronary artery disease and in 15 normal subjects. Patients with LVH had more heterogeneous left ventricular activity of IPPA compared to normal subjects after exercise but not at rest (23±8% versus 13±5% difference in maximum segmental activity at 4 minutes after exercise; p=0.005). Although IPPA clearance was similar in both patients with LVH and normal subjects, postexercise washout in segments showing decreased initial IPPA uptake was reduced compared to washout at rest in patients with LVH (11.7±7.5% versus 21.5±8.4% at 20 minutes after injection, n=15; p=0.005). Exercise thallium-201 (Tl-201) scintigraphy was normal in all seven patients with LVH tested. Patients with LVH showed significantly greater heterogeneity in IPPA uptake compared to TI-201 uptake immediately after exercise (25±5% versus 16±6%; p=0.013). We conclude that (1) compared to normal subjects, patients with LVH show heterogeneous myocardial IPPA activity after exercise but not at rest; (2) postexercise washout of IPPA was decreased in segments with reduced uptake after exercise in patients with LVH; and (3) the distribution of IPPA is more heterogeneous than that of TI-201 immediately after exercise in patients with concentric LVH. The postexercise heterogeneity in IPPA uptake and delayed washout in segments with reduced initial uptake is consistent with exercise-induced myocardial ischemia in patients with LVH.